2021
DOI: 10.1001/jamasurg.2021.0231
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sarcopenia and Body Composition With Postoperative 90-Day Morbidity After Liver Resection for Malignant Tumors

Abstract: and practitioners to identify individuals in urgent need of medical attention. The evidence available indicates that the ODI has excellent psychometric and structural properties, which is not the case for the Maslach Burnout Inventory, the most widely used measure of burnout. 4 Occupational health specialists have persistently come up against the problem of how to define and diagnose burnout, as illustrated again by the findings by Hewitt et al. 1 Somewhat surrealistically, studies claiming to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…A study involving 234 patients after liver resection for malignant tumours reported that patients with sarcopenia had a statistically significantly higher rate of 90‐day morbidity than patients in the other groups and had longer hospital stays and higher readmission rates. 25 Another study involving 404 patients undergoing radical gastrectomy for gastric cancer also found that sarcopenia significantly increased post‐operative morbidity in gastric cancer patients, resulting in longer post‐operative hospital stay and shorter overall survival and disease‐free survival. 26 The reasons for the high morbidity in elderly patients with sarcopenia may be as follows: (1) The decrease of amino acids released by skeletal muscle of sarcopenia patients lead to the lack of raw materials for the synthesis of acute phase proteins by the liver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study involving 234 patients after liver resection for malignant tumours reported that patients with sarcopenia had a statistically significantly higher rate of 90‐day morbidity than patients in the other groups and had longer hospital stays and higher readmission rates. 25 Another study involving 404 patients undergoing radical gastrectomy for gastric cancer also found that sarcopenia significantly increased post‐operative morbidity in gastric cancer patients, resulting in longer post‐operative hospital stay and shorter overall survival and disease‐free survival. 26 The reasons for the high morbidity in elderly patients with sarcopenia may be as follows: (1) The decrease of amino acids released by skeletal muscle of sarcopenia patients lead to the lack of raw materials for the synthesis of acute phase proteins by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that sarcopenia was an independent risk factor for post‐operative morbidity, which is consistent with other studies. A study involving 234 patients after liver resection for malignant tumours reported that patients with sarcopenia had a statistically significantly higher rate of 90‐day morbidity than patients in the other groups and had longer hospital stays and higher readmission rates 25 . Another study involving 404 patients undergoing radical gastrectomy for gastric cancer also found that sarcopenia significantly increased post‐operative morbidity in gastric cancer patients, resulting in longer post‐operative hospital stay and shorter overall survival and disease‐free survival 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 , 15 Especially for patients undergoing surgery, sarcopenia is a common occurrence and has a significant influence on prognosis. Recent studies have indicated that sarcopenia has a negative effect on postoperative outcomes including those for lung cancer, 16 esophageal cancer, 17 liver malignant tumors, 18 and colorectal liver metastases. 19 …”
Section: Introductionmentioning
confidence: 99%